Qashqadaryo viloyati umumta’lim muassasalari va ularning infratuzilmasi hududiy jihatlari - Nurmatov, A.U (SCIENCE and SOCIETY, 2025)
This article will provide a geographical analysis of the number of public educational institutions in the Kashkadarya region, their territorial distribution and the state of development of infrastructure. Changes in the number of schools in the district and urban cross-section are assessed based on their correlation with demographic factors, available infrastructure capabilities, and territorial requirements for education. Based on statistics, the number of public institutions in the region is increasing from year to year, but this increase is not going uniformly in the cross-section of the regions. The article also analyzes the quality of the school infrastructure, the physical condition of the premises, the level of provision of modern educational equipment and their territorial differences. Based on the results of the study, practical recommendations were made to ensure the territorial balance of the general education system in the region and to improve
Keywords: Kashkadarya region; General Educational Institutions; Infrastructure; territorial development; demographic factors; educational geography; school network; territorial imbalance; social infrastructure; educational system